Ways in Which Teachers Structure Reading Instruction for Bilingual Students with Disabilities: A Case Study Analysis - (:unkn) unknown (My University, 2015)
In partial fulfillment of candidacy for Ph.D. at the University of Wisconsin at Milwaukee, this research study uses a single case study design to answer the question, How do teachers structure reading instruction for bilingual students with disabilities in urban elementary settings? Bronfenbrenner’s Bioecological Theory and critical race theory guided the study design and data analysis of interviews, observations, and documents to determine that teachers of bilingual students with disabilities experience unique challenges. Findings of the study include the topics of disability blindfolding; disjointed delivery; improper instruction due to assessment and progress monitoring; spatial implications; definitions impact instruction; and teachers’ personal characteristics influence reading instruction. In addition to a discussion of the salient themes, implications for practice and theory, the significance of the study, and recommendations for future research are presented.
Keywords: Bilingual Special Education; Bilingual Students with Disabilities; Case Study; Qualitative; Reading Instruction; Special Education